2021
DOI: 10.18502/jfsh.v5i4.5701
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistant bacteria in raw cow milk and milk products retailed in the northern region of Ghana; a food safety challenge

Abstract: The presence of antimicrobial resistant foodborne bacteria is a major food safety challenge for food that is consumed raw. Abuse and overuse of antibiotics in the agriculture sector has been identified as a contributory factor to the rising threat of antibiotic resistance. In many developing countries where milk is marketed and consumed raw through informal channels, the occurrence of bacterial contamination is high and poses a major public health risk. This situation is exacerbated when caused by antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Similarly, Bonyadian and collaborators, reported that E. coli isolates from raw cow's milk and unpasteurized cheese showed resistance to ampicillin (66%), gentamicin (69.6%) and ciprofloxacin (56.7%) [23]. Resistance rates in our study are lower than those reported in Nigeria, but far higher than those reported in the northern region of Ghana [24,20]. In this study we also detected high sensitivity of E. coli to ofloxacin (100, 78 and 70%), chloramphenicol (57, 78 and 90%) and gentamicin (86, 100 and 100%) (Fig 1).…”
Section: Antibiotic Susceptibility Of Escherichia Coli Strainssupporting
confidence: 42%
See 2 more Smart Citations
“…Similarly, Bonyadian and collaborators, reported that E. coli isolates from raw cow's milk and unpasteurized cheese showed resistance to ampicillin (66%), gentamicin (69.6%) and ciprofloxacin (56.7%) [23]. Resistance rates in our study are lower than those reported in Nigeria, but far higher than those reported in the northern region of Ghana [24,20]. In this study we also detected high sensitivity of E. coli to ofloxacin (100, 78 and 70%), chloramphenicol (57, 78 and 90%) and gentamicin (86, 100 and 100%) (Fig 1).…”
Section: Antibiotic Susceptibility Of Escherichia Coli Strainssupporting
confidence: 42%
“…The high resistance detected among E. coli strains has been reported in other studies in Africa. In the northern region of Ghana, isolates from milk and milk products showed greater resistance to chloramphenicol, gentamicin, trimethoprim-sulfamethoxazole and ceftriaxone, but were most susceptible to ciprofloxacin and ampicillin [20]. In Ethiopia, Tadesse and collaborators, showed that E. coli strains isolated from dairy, fruit juice and cow's milk were highly resistant to gentamicin (100%), ciprofloxacin (90%), ampicillin (70%), tetracycline (60%) and chloramphenicol (50%) [21].…”
Section: Antibiotic Susceptibility Of Escherichia Coli Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and fifty (150) bacterial isolates from raw milk and milk products were evaluated against nine antimicrobials that are often used in veterinary and human medical practice in the Northern region of Ghana. The isolates exhibited the highest levels of resistance to nalidixic acid, followed by chloramphenicol, gentamicin, trimethoprim-sulfamethoxazole, and ceftriaxone, but were primarily susceptible to ciprofloxacin and ampicillin [15]. In a study by Thonda et al [16] in Osun State, E. coli isolates obtained from cow milk, yoghurt, and cheese were found to be multiple antibiotic-resistant kinds, revealing seventeen different multiple antibiotic resistance patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Reagents for gene amplification were constituted in reaction mixtures A and B (AM-A and AM-B). Regions of the DNA associated with mutations that are most frequently identified in resistant strains conferring resistance to isoniazid and rifampicin were amplified in the presence of 10 µL AM-A, 35…”
Section: Line Probe Assay Pcrmentioning
confidence: 99%